Peer Harassment among Youths with Different Disabilities: Impact of Harassment Online, in Person, and in Mixed Online and In-Person Incidents. Issue 1 (14th November 2018) - Wells, Melissa; Mitchell, Kimberly J; Jones, Lisa M; Turner, Heather A
Abstract: This study examines how youths with different types of disabilities, mental health diagnoses, and special education services experience peer harassment victimization (PHV). This analysis examines how these youths experience harassment that only occurs in person, only through technology, and both in person and through technology ("mixed"). Data were collected as part of the Technology Harassment Victimization study, a U.S. telephone survey of 791 youths, ages 10 to 20. Results indicate that compared with youths not reporting peer harassment, youths diagnosed with depression were more likely to report a mixed mode form of peer harassment, youths with a physical disability were more likely to report harassment through technology, and youths with a learning disability were more likely to report in-person harassment. The type of disability, diagnosis, or special service among youths may be associated with unique vulnerabilities in terms of peer harassment experiences. School social workers and other school personnel should consider specific types of disabilities in assessing risks of PHV and in planning interventions.